The role of stage-specific oligonucleotide primers in providing effective laboratory support for the molecular diagnosis of reactivated Toxoplasma gondii encephalitis in patients with AIDS - CONTINI, CARLO; CULTRERA, ROSARIO; SERACENI, SILVA; SEGALA, DANIELA; ROMANI, ROBERTO; FAINARDI, ENRICO; CINQUE, PAOLA; LAZZARIN, ADRIANO; DELIA, SALVATORE (Journal of medical microbiology, 2002)
Section of Infectious Diseases, Department of Clinical & Experimental Medicine, University of Ferrara, via Fossato di Mortara 23, 44100 Ferrara, *Department of Infectious and Tropical Diseases, La Sapienza University, Policlinico Umberto 1°, via Regina Elena 331, 00161 Rome, Division of Infectious Diseases, San Raffaele Hospital, Via Stamira d'Ancona, 20, 20127 Milano and Section of Neurologic Clinic, University of Ferrara, Arcispedale S. Anna, C.so Giovecca 203, Ferrara, Italy Corresponding author: Professor C. Contini (e-mail: cncatdns.unife.it ). Received 24 Jan. 2002; revised version received 28 May 2002; accepted 6 June 2002. The switch from bradyzoites to tachyzoites is the fundamental pathogenic event that leads to Toxoplasma gondii encephalitis (TE) in patients with AIDS. Distinction between these stages is difficult, particularly when specific treatment has been started. A new approach consisting of a nested PCR (n-PCR) assay was performed on cerebrospinal fluid (CSF) specimens collected from AIDS patients with TE before or after antiparasitic therapy was initiated, to assess the efficacy of primer sets which amplify target sequences expressed on bradyzoites (SAG4 and MAG1), tachyzoites (SAG1) or both stages (B1) of T. gondii . CSF specimens were obtained from 46 patients with AIDS, of whom 27 had TE (16 first episode, 11 relapse) and 19 had other AIDS-related brain lesions (AIDS-OBL) in the absence of TE. CSF specimens from 26 HIV-negative and immunocompetent patients were also checked. All samples were tested with different primer pairs targeting the B1, SAG-1, SAG-4 and MAG-1 genes. With B1, 75% of patients with first episodes of TE were positive, compared with 36.3% of those with relapse of TE and 5.2% of those with AIDS-OLB. The SAG1 gene yielded positive values in 28.7% and 45.4% of patients with first episodes of TE or relapse of TE, respectively, and in none of the controls. With the SAG4 and MAG1 genes, 72.7% of patients with relapse of TE were detected, compared with 25% of patients with first episodes of TE and 5.2% with AIDS-OLB. None of the HIV-negative subjects showed positive PCR reactions. These results demonstrate that specific primers for the genes SAG4, MAG1 and SAG1 may be useful in AIDS patients with relapse of TE, in whom the use of PCR targeting the B1 gene may fail to detect DNA, especially when prophylaxis or treatment has been started.